Impact of Corporate Social Responsibility on Corporate Image and Identity - CHOUDHARY, ANAND (IJRDO - Journal of Business Management, 2019)
The current article is a conceptual work exploring the potential impact of corporate social responsibility (CSR) on corporate image and identity globally. The findings reveal that CSR has a strong and positive impact on company image as it creates a positive image of the organisation in the minds of the stakeholders including employees, suppliers, partners, shareholders, local communities among others. The findings also bring to light that CSR adds value to the organisation by reducing the cost and risk of doing business, adds to the reputation of the companies, harnesses greater competitive advantage, and creates a win-win situation for all stakeholders. The results may have important implications for multinational corporations (MNCs) operating in developing countries, development agencies including the United Nations (UN), UNCTAD and researchers working in the field of CSR, stakeholder management, brand management, etc.